Aluminum-based MOF (Metal Organic Framework) composite adsorbent as well as preparation method and application thereof

By mixing Al-MOF with sodium alginate and carrageenan to form a double network hydrogel and forming it, the problem of insufficient mechanical strength after MOF material is solved, and a high compression resistance and cyclic stability of aluminum-based MOF composite adsorbent is achieved.

CN119869483APending Publication Date: 2025-04-25ZINGKE (CHONGQING) ADVANCED MATERIALS RES INST CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510256122.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing MOF materials are insufficient in the molding process, the molded particles are prone to shatter, and the adsorption performance is prone to change after molding, resulting in limited material application.

Method used

By mixing Al-MOF with sodium alginate and carrageenan, a double network hydrogel is formed, and molded through the pill making equipment to form a high-strength aluminum-based MOF composite adsorbent.

Benefits of technology

The high compressive performance and mechanical stability of the aluminum-based MOF composite adsorbent is achieved, and water vapor is spontaneously adsorbed under low humidity, with strong circulation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869483A_ABST
    Figure CN119869483A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water adsorption materials, in particular to an aluminum-based MOF composite adsorbent and a preparation method and application thereof.The aluminum-based MOF composite adsorbent is obtained by weighing Al-MOF, adding the Al-MOF into a lithium chloride solution, conducting ultrasonic dispersion, stirring, filtering and drying at the temperature of 80-120 DEG C; adding sodium alginate and carrageenan into deionized water, and stirring to obtain double-network hydrogel; and adding the double-network hydrogel into the aluminum-based MOF adsorbent, uniformly mixing, forming by pelleting equipment to prepare adsorbent particles, and drying the adsorbent particles at the temperature of 80-120 DEG C to obtain the aluminum-based MOF composite adsorbent. According to the invention, Al-MOF, sodium alginate and carrageenan are mixed and molded, so that a high-strength hydrogel network can be obtained, and Al < 3 + > in an MOF skeleton and functional groups in sodium alginate and carrageenan in the dual-network hydrogel are coordinated, so that the network structure is tighter and more stable; the free movement of water molecules in the hydrogel can be effectively limited, so that the swelling property and the mechanical stability of the hydrogel are further adjusted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water adsorption materials, and in particular to an aluminum-based MOF composite adsorbent and a preparation method and application thereof. Background Art

[0002] Most of the water on Earth is inaccessible due to high salt content or because it is locked in the form of ice. Most fresh water comes from lakes and rivers, which are not necessarily available in most arid regions of the world. Water in the atmosphere is a natural resource, with approximately 12,900 km of air present at all times. 3 Water is collected from the atmosphere and continuously replenished through the hydrological cycle. Air water extraction (AWH) is considered to be an effective way to obtain fresh water to alleviate water shortages.

[0003] Adsorption-based air water extraction technology can capture fresh water resources from the air in arid areas, and is expected to provide a new way to provide a stable supply of fresh water in water-scarce areas. The core of this technology is the design and preparation of high-performance water-absorbing materials. Metal-organic framework materials (MOFs) are composed of organic ligands and metal clusters connected by coordination bonds, and have the advantages of high specific surface area, adjustable pore structure and easy functionalization. MOF materials mainly interact with water molecules through functional sites to capture water molecules in the air. This interaction is weaker than chemical adsorption, so it has a lower adsorption heat, thereby achieving low-temperature regeneration of the adsorption material and reducing energy consumption. In addition, through reasonable pore structure design, rich action sites can be constructed within the MOF material framework, and multiple adsorption sites can be used to adsorb water molecules at the same time, ultimately achieving a high adsorption capacity. The characteristics of high adsorption capacity, fast adsorption / desorption kinetics and low regeneration energy consumption make MOF materials have great application prospects in the field of air water absorption in arid areas.

[0004] Existing MOFs exist in the form of powder microcrystals, which are not conducive to industrial production and are difficult to recycle. Therefore, molding has become a key step for MOF to move towards industrial application. At present, in addition to the traditional in-situ growth method, adhesive molding method, and high-pressure granulation method, MOF molding also has new processing methods such as electrospinning, freeze-drying, and hot pressing. The new processing methods are still in the laboratory stage due to their high technical content and difficulty in operation; traditional methods such as extrusion molding and ball molding have long been widely used in the molding process of other materials, but because the strength of MOF materials is far inferior to that of traditional porous materials, the MOF framework structure can easily collapse under high pressure, causing pore collapse, and adhesive molding often has pore blocking. Therefore, the existing MOF material molding technology still has the following shortcomings:

[0005] First, there is a lack of suitable molding formulas and technologies, which results in most of the research and development process remaining in the laboratory and adsorbent powder stage, resulting in limited application; second, the mechanical strength after molding is insufficient, and the materials after molding are stacked. Under the action of their own gravity, the bottom material is compressed and broken. Secondly, there are extrusion and collision during use and transportation, which leads to particle breakage. The broken adsorbent has problems such as easy loss of the adsorbent and change in adsorption performance, which makes the adsorbent unable to operate for a long time; third, during the adsorbent molding process, the adsorbent content is low, and the addition of additives causes the pores of the porous material to be blocked, resulting in a significant decrease in adsorption performance. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide an aluminum-based MOF composite adsorbent and a preparation method and application thereof, so as to at least solve the problems of insufficient mechanical strength and easy breakage of formed particles existing in the prior art water-absorbing MOF materials.

[0007] The present invention solves the above technical problems by the following technical means:

[0008] In a first aspect, an embodiment of the present invention provides a method for preparing an aluminum-based MOF composite adsorbent, comprising the following steps:

[0009] Weigh lithium chloride, add it into deionized water, stir and dissolve it to obtain a lithium chloride solution, weigh Al-MOF, add it into the lithium chloride solution, disperse it by ultrasonic wave, stir, filter it, and dry it at 80-120° C. to obtain an aluminum-based MOF adsorbent;

[0010] Sodium alginate and carrageenan were weighed separately, added into deionized water at 75-85°C, stirred and dispersed evenly, and cooled to room temperature to obtain a double network hydrogel;

[0011] The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed evenly, and the adsorbent particles are formed into adsorbent particles through a pelletizing device. The adsorbent particles are dried at a temperature of 80 to 120° C. to obtain an aluminum-based MOF composite adsorbent.

[0012] Preferably, the mass ratio of the Al-MOF to lithium chloride is 1:(1.5-2.5), and the concentration of the lithium chloride solution is 30-45wt%.

[0013] Preferably, the preparation method of the Al-MOF is as follows:

[0014] Add fumaric acid and aminosuccinic acid into deionized water, add sodium hydroxide, and stir to dissolve at a temperature of 30 to 80° C. to obtain a ligand solution;

[0015] Add aluminum chloride hydrate into deionized water, stir and dissolve at room temperature to obtain a metal salt solution;

[0016] The metal salt solution is added to the ligand solution, stirred at a temperature of 30 to 80° C. for 2 to 5 hours, the obtained solid product is washed with deionized water for 2 to 3 times, and dried at a temperature of 80 to 120° C. to obtain Al-MOF.

[0017] Preferably, the molar ratio of fumaric acid to aminosuccinic acid is (4-5.5):1.

[0018] Preferably, the molar ratio of the sodium hydroxide to the total ligand is (0.5-1.5):1, and the molar amount of the total ligand is the sum of the molar amounts of fumaric acid and aminosuccinic acid.

[0019] Preferably, the molar ratio of the aluminum chloride hexahydrate to the total ligands is 1:(3-5).

[0020] Preferably, the molar ratio of sodium alginate to carrageenan is (0.5-2):1.

[0021] Preferably, the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 4% to 10%.

[0022] In a second aspect, an embodiment of the present invention provides an aluminum-based MOF composite adsorbent, and the aluminum-based MOF composite adsorbent is prepared by the preparation method described in the first aspect above.

[0023] In a third aspect, an embodiment of the present invention provides the use of the aluminum-based MOF composite adsorbent described in the second aspect in a water adsorption material.

[0024] In the preparation method of the aluminum-based MOF composite adsorbent of the present invention, Al-MOF is mixed with sodium alginate and carrageenan and then molded, which can not only obtain a high-strength hydrogel network, but also can obtain a high-strength hydrogel network through the Al in the MOF skeleton. 3+ The coordination with the functional groups in sodium alginate and carrageenan in the double network hydrogel makes the network structure more compact and stable. This stable network structure can effectively limit the free movement of water molecules in the gel, thereby further adjusting the swelling properties and mechanical stability of the hydrogel. According to the test, its compressive resistance can reach more than 187N.

[0025] The aluminum-based MOF composite adsorbent prepared by the present invention can spontaneously adsorb water vapor under low humidity, and the adsorption performance is not significantly reduced after 10 uses, and has strong cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the XRD pattern of the Al-MOF and aluminum-based MOF composite adsorbent prepared in Example 1;

[0027] Figure 2is a BET diagram of the Al-MOF and aluminum-based MOF composite adsorbent prepared in Example 1;

[0028] Figure 3 This is a product photo of the aluminum-based MOF composite adsorbent prepared in Example 1;

[0029] Figure 4 This is a diagram of the cyclic adsorption performance of the Al-MOF and aluminum-based MOF composite adsorbents prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0032] As a new type of polymer material, the double network gel not only has two networks of cross-linked polymers, but also the performance of the double network gel can be changed by adjusting the cross-linking strategy. Specifically, by combining ionic cross-linking with various non-covalent interaction methods, the synergistic effect between the cross-linked networks can be better achieved to form a gel with better performance. Carrageenan is a hydrophilic colloid and a linear polysaccharide containing sulfate groups. It is composed of d-galactose and 3,6-dehydrogalactose units and has good biodegradability, biocompatibility and non-toxicity, making it suitable for the synthesis of hydrogel adsorbents. Carrageenan can also be used to react with cations (such as K + , Ca 2+ 、Co 2+ 、Zn 2+ and Fe 3+ ) forms a double helix structure, but the mechanical properties of carrageenan are weak, and the hydrogel formed by carrageenan is easily deformed, which usually limits its application. Sodium alginate is a degradable linear natural polymer with high stability, good biocompatibility, gelation, oil resistance and hydrophilicity. 2+ 、Zn 2+ 、Co 2+ 、Al3+ The cationic physical crosslinking can form an insoluble alginate gel. Therefore, adding sodium alginate to carrageenan can generate a double network composite hydrogel system with good mechanical strength. This structure makes the gel have better mechanical properties and stability.

[0033] In the aluminum-based MOF composite adsorbent of the present application, during the molding process, the double network structure of carrageenan and sodium alginate changes the swelling properties of the hydrogel, so that the mechanical properties and stability of the double network hydrogel are significantly improved, and because Al 3+ By coordinating with the functional groups in sodium alginate and carrageenan, the network structure of the gel is made tighter and more stable. This stable network structure can effectively limit the free movement of water molecules in the gel, thereby further adjusting the swelling properties and mechanical stability of the hydrogel.

[0034] Specifically, the preparation method of the aluminum-based MOF composite adsorbent of the present application comprises the following steps:

[0035] S1: Weigh lithium chloride and add it into deionized water, stir and dissolve to obtain a lithium chloride solution, weigh Al-MOF and add it into the lithium chloride solution, disperse it by ultrasonic wave, stir, filter, and dry it at 80-120° C. to obtain an aluminum-based MOF adsorbent;

[0036] S2: Weigh sodium alginate and carrageenan respectively, add them into deionized water at 75-85°C, stir and disperse them evenly, and cool them to room temperature to obtain a double network hydrogel. In this step, the mass ratio of deionized water to Al-MOF is 1:(1.2-2);

[0037] S3: Add the double network hydrogel to the aluminum-based MOF adsorbent and mix well, and form the adsorbent particles through a pelletizing device. Dry the adsorbent particles at a temperature of 80 to 120° C. to obtain an aluminum-based MOF composite adsorbent.

[0038] Among them, the mass ratio of Al-MOF and lithium chloride is 1:(1.5-2.5), the concentration of lithium chloride solution is 30-45wt%, the molar ratio of sodium alginate and carrageenan is (0.5-2):1, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 4%-10%.

[0039] The preparation method of Al-MOF is as follows: fumaric acid and aminosuccinic acid are added to deionized water, and sodium hydroxide is added, and the mixture is stirred and dissolved at a temperature of 30 to 80°C to obtain a ligand solution; aluminum chloride hydrate is added to deionized water, and the mixture is stirred and dissolved at room temperature to obtain a metal salt solution; the metal salt solution is added to the ligand solution, and the mixture is stirred at a temperature of 30 to 80°C for 2 to 5 hours, and the obtained solid product is washed with deionized water for 2 to 3 times, and dried at a temperature of 80 to 120°C to obtain Al-MOF. Among them, the molar ratio of fumaric acid to aminosuccinic acid is (4 to 5.5):1, the molar ratio of sodium hydroxide to total ligands is (0.5 to 1.5):1, the molar amount of total ligands is the sum of the molar amounts of fumaric acid and aminosuccinic acid, and the molar ratio of aluminum chloride hexahydrate to total ligands is 1:(3 to 5).

[0040] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0041] Example 1

[0042] The preparation method of the aluminum-based MOF composite adsorbent of this embodiment is as follows:

[0043] (1) According to the molar ratio of fumaric acid to aminosuccinic acid of 5:1, fumaric acid and aminosuccinic acid are weighed respectively, and fumaric acid and aminosuccinic acid are added to deionized water, followed by sodium hydroxide, the molar amount of sodium hydroxide being equal to the total molar amount of fumaric acid and aminosuccinic acid, and stirred and dissolved at 60°C to obtain a ligand solution. Aluminum chloride hexahydrate is added to deionized water and stirred and dissolved to obtain a metal salt solution. The metal salt solution is added to the ligand solution under stirring at 60°C, and the stirring is continued at 60°C for 4 hours. The solid product obtained by filtration is washed 3 times with deionized water, and dried at a temperature of 90°C to obtain an aluminum-based MOF, i.e., Al-MOF. The molar ratio of aluminum chloride hexahydrate to the total molar amount of fumaric acid and aminosuccinic acid in this embodiment is 1:4.

[0044] (2) Weigh lithium chloride and add it to deionized water, stir and dissolve to obtain a lithium chloride solution with a concentration of 40 wt%, weigh Al-MOF and add it to the lithium chloride solution, and ultrasonically disperse the Al-MOF evenly in the lithium chloride salt solution, stir for 10 hours, filter, and dry at 100° C. to obtain an aluminum-based MOF adsorbent.

[0045] (3) Sodium alginate and carrageenan are weighed and added to deionized water at a molar ratio of 2:1, and then stirred at 80°C under magnetic stirring until uniformly dispersed, and then cooled to room temperature to obtain a double network hydrogel. The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed. In this step, the mass ratio of deionized water to the aluminum-based MOF adsorbent is 1:1.5, and the adsorbent particles are formed by a pelletizing device. The adsorbent particles are dried at 80°C for 2h and 120°C for 10h to obtain an aluminum-based MOF composite adsorbent, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 5%.

[0046] The XRD pattern of the aluminum-based MOF composite adsorbent prepared in this example is as follows: Figure 1 As shown in the BET diagram Figure 2 As shown, the photo of the aluminum-based MOF composite adsorbent obtained after molding is as follows Figure 3 As shown, it is applied to the adsorption material of air water extraction, and the obtained cyclic use adsorption performance diagram is shown in Figure 4 shown.

[0047] exist Figure 1 The data of the XRD diagram show that the aluminum-based MOF composite adsorbent prepared in this embodiment exhibits characteristic peaks of Al-MOF at 2θ=10.30°, 14.81°, 21.01°, 31.74° and 42.79°, indicating that the crystalline structure of the Al-MOF composite adsorbent prepared in this embodiment does not change significantly before and after molding, and the double network hydrogel and hygroscopic salt lithium chloride do not cause the collapse of the pore structure.

[0048] exist Figure 2 The data of the BET graph show that the specific surface area of ​​the untreated Al-MOF is 427.76 m 2 / g, pore volume 0.5327cm 3 / g, the double network hydrogel was formed and then crushed in a mortar. The specific surface area and pore volume were 280.77m 2 / g, 0.4725cm 3 / g, the addition of double network hydrogel only reduced the pore volume by 11.30%. It is speculated that a part of the double network hydrogel entered the pores of Al-MOF, but nearly 90% of the pores were still retained.

[0049] Figure 3 It can be seen from the photos that the aluminum-based MOF composite adsorbent prepared in this example has uniform particles with a particle size of 8 mm.

[0050] exist Figure 4In the cyclic adsorption performance data diagram, the adsorption process, the adsorption conditions are set to 30°C, 30% RH, and the adsorption time is set to 10h. In the desorption process, the conditions are set to 100°C, 30% RH, and the desorption time is 1h. The single adsorption amount is 620-680 mg / g, and the adsorption amount is still maintained above 98% after 10 cycles, indicating that the aluminum-based MOF composite adsorbent prepared in this example has strong cyclic stability.

[0051] Example 2

[0052] The preparation method of the aluminum-based MOF composite adsorbent of this embodiment is as follows:

[0053] (1) According to the molar ratio of fumaric acid to aminosuccinic acid of 5:1, fumaric acid and aminosuccinic acid are weighed respectively, and fumaric acid and aminosuccinic acid are added to deionized water, followed by sodium hydroxide, the molar amount of sodium hydroxide being equal to the total molar amount of fumaric acid and aminosuccinic acid, and stirred and dissolved at 60°C to obtain a ligand solution. Aluminum chloride hexahydrate is added to deionized water and stirred and dissolved to obtain a metal salt solution. The metal salt solution is added to the ligand solution under stirring at 60°C, and the stirring is continued at 60°C for 4 hours. The solid product obtained by filtration is washed 3 times with deionized water, and dried at a temperature of 90°C to obtain an aluminum-based MOF, i.e., Al-MOF. The molar ratio of aluminum chloride hexahydrate to the total molar amount of fumaric acid and aminosuccinic acid in this embodiment is 1:4.

[0054] (2) Weigh lithium chloride and add it to deionized water, stir and dissolve to obtain a lithium chloride solution with a concentration of 40 wt%, weigh Al-MOF and add it to the lithium chloride solution, and ultrasonically disperse the Al-MOF evenly in the lithium chloride salt solution, stir for 10 hours, filter, and dry at 100° C. to obtain an aluminum-based MOF adsorbent.

[0055] (3) Sodium alginate and carrageenan are weighed and added to deionized water at a molar ratio of 2:1, and then stirred at 80°C under magnetic stirring until uniformly dispersed, and then cooled to room temperature to obtain a double network hydrogel. The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed. In this step, the mass ratio of deionized water to the aluminum-based MOF adsorbent is 1:1.5, and the adsorbent particles are formed by a pelletizing device. The adsorbent particles are dried at 80°C for 2h and 120°C for 10h to obtain an aluminum-based MOF composite adsorbent, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 5%.

[0056] Example 3

[0057] The preparation method of the aluminum-based MOF composite adsorbent of this embodiment is as follows:

[0058] (1) According to the molar ratio of fumaric acid to aminosuccinic acid of 5:1, fumaric acid and aminosuccinic acid are weighed respectively, and fumaric acid and aminosuccinic acid are added to deionized water, followed by sodium hydroxide, the molar amount of sodium hydroxide being equal to the total molar amount of fumaric acid and aminosuccinic acid, and stirred and dissolved at 60°C to obtain a ligand solution. Aluminum chloride hexahydrate is added to deionized water and stirred and dissolved to obtain a metal salt solution. The metal salt solution is added to the ligand solution under stirring at 60°C, and the stirring is continued at 60°C for 4 hours. The solid product obtained by filtration is washed 3 times with deionized water, and dried at a temperature of 90°C to obtain an aluminum-based MOF, i.e., Al-MOF. The molar ratio of aluminum chloride hexahydrate to the total molar amount of fumaric acid and aminosuccinic acid in this embodiment is 1:4.

[0059] (2) Weigh lithium chloride and add it to deionized water, stir and dissolve to obtain a lithium chloride solution with a concentration of 40 wt%, weigh Al-MOF and add it to the lithium chloride solution, and ultrasonically disperse the Al-MOF evenly in the lithium chloride salt solution, stir for 10 hours, filter, and dry at 100° C. to obtain an aluminum-based MOF adsorbent.

[0060] (3) Sodium alginate and carrageenan are weighed and added to deionized water at a molar ratio of 1:2, and then stirred at 80°C under magnetic stirring until uniformly dispersed, and then cooled to room temperature to obtain a double network hydrogel. The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed. In this step, the mass ratio of deionized water to the aluminum-based MOF adsorbent is 1:1.5, and the adsorbent particles are formed by a pelletizing device. The adsorbent particles are dried at 80°C for 2h and 120°C for 10h to obtain an aluminum-based MOF composite adsorbent, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 5%.

[0061] Example 4

[0062] The preparation method of the aluminum-based MOF composite adsorbent of this embodiment is as follows:

[0063] (1) According to the molar ratio of fumaric acid to aminosuccinic acid of 4:1, fumaric acid and aminosuccinic acid are weighed respectively, and fumaric acid and aminosuccinic acid are added to deionized water, followed by sodium hydroxide, wherein the molar amount of sodium hydroxide is 0.5 times the total molar amount of fumaric acid and aminosuccinic acid, and stirred and dissolved at 30°C to obtain a ligand solution. Aluminum chloride hexahydrate is added to deionized water and stirred and dissolved to obtain a metal salt solution. The metal salt solution is added to the ligand solution under stirring at 30°C, and the stirring is continued at 30°C for 4 hours. The solid product obtained by filtration is washed twice with deionized water and dried at a temperature of 80°C to obtain an aluminum-based MOF, i.e., Al-MOF. The molar ratio of aluminum chloride hexahydrate to the total molar amount of fumaric acid and aminosuccinic acid in this embodiment is 1:3.

[0064] (2) Weigh lithium chloride and add it to deionized water, stir and dissolve to obtain a lithium chloride solution with a concentration of 30 wt%, weigh Al-MOF and add it to the lithium chloride solution, and ultrasonically disperse the Al-MOF evenly in the lithium chloride salt solution, stir for 10 hours, filter, and dry at 80° C. to obtain an aluminum-based MOF adsorbent.

[0065] (3) Sodium alginate and carrageenan are weighed and added to deionized water at a molar ratio of 1:2, and then stirred at 75°C under magnetic stirring until uniformly dispersed, and then cooled to room temperature to obtain a double network hydrogel. The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed. In this step, the mass ratio of deionized water to the aluminum-based MOF adsorbent is 1:1.2, and the adsorbent particles are formed by a pelletizing device. The adsorbent particles are dried at 80°C for 2h and 120°C for 10h to obtain an aluminum-based MOF composite adsorbent, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 4%.

[0066] The aluminum-based MOF composite adsorbent prepared in this example was subjected to water vapor adsorption performance test. Before the test, the aluminum-based MOF composite adsorbent particles need to be placed in an oven and dried at 120°C until no significant change in the adsorbent mass is detected. Then, 10g of the adsorbent molded particles are weighed and evenly spread on a flat dish and tested in a constant temperature and humidity chamber. The temperature of the constant temperature and humidity chamber is set to 30°C and the humidity is set to 30% RH. The test results show that the vapor adsorption amount is 589mg / g.

[0067] Example 5

[0068] The preparation method of the aluminum-based MOF composite adsorbent of this embodiment is as follows:

[0069] (1) According to the molar ratio of fumaric acid to aminosuccinic acid of 5.5:1, fumaric acid and aminosuccinic acid are weighed respectively, and fumaric acid and aminosuccinic acid are added to deionized water, followed by sodium hydroxide, wherein the molar amount of sodium hydroxide is 1.5 times the total molar amount of fumaric acid and aminosuccinic acid, and stirred and dissolved at 80°C to obtain a ligand solution. Aluminum chloride hexahydrate is added to deionized water, and stirred and dissolved at room temperature to obtain a metal salt solution. The metal salt solution is added to the ligand solution under stirring at 30°C, and the stirring is continued at 30°C for 4 hours. The solid product obtained by filtration is washed 3 times with deionized water, and dried at a temperature of 120°C to obtain an aluminum-based MOF, i.e., Al-MOF. The molar ratio of aluminum chloride hexahydrate to the total molar amount of fumaric acid and aminosuccinic acid in this embodiment is 1:5.

[0070] (2) Weigh lithium chloride and add it to deionized water, stir and dissolve to obtain a lithium chloride solution with a concentration of 45 wt%, weigh Al-MOF and add it to the lithium chloride solution, and ultrasonically disperse the Al-MOF evenly in the lithium chloride salt solution, stir for 10 hours, filter, and dry at 120° C. to obtain an aluminum-based MOF adsorbent.

[0071] (3) Sodium alginate and carrageenan are weighed and added to deionized water at a molar ratio of 1:2, and then cooled to room temperature to obtain a double network hydrogel. The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed. In this step, the mass ratio of deionized water to the aluminum-based MOF adsorbent is 1:2, and the adsorbent particles are formed by a pelletizing device. The adsorbent particles are dried at 80°C for 2h and 120°C for 10h to obtain an aluminum-based MOF composite adsorbent, and the mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 10%.

[0072] The aluminum-based MOF composite adsorbent prepared in this example was subjected to water vapor adsorption performance test. Before the test, the aluminum-based MOF composite adsorbent particles need to be placed in an oven and dried at 120°C until no significant change in the adsorbent mass is detected. Then, 10g of the adsorbent molded particles are weighed and evenly spread on a flat dish, and the test is carried out in a constant temperature and humidity chamber. The temperature of the constant temperature and humidity chamber is set to 30°C, and the humidity is set to 30% RH. The test results show that the vapor adsorption amount is 563mg / g.

[0073] The water vapor adsorption performance of the Al-MOF powder and the aluminum-based MOF composite adsorbent prepared in Examples 1-3 was measured respectively. Before the test, the aluminum-based MOF composite adsorbent particles needed to be placed in an oven and dried at 120°C until no significant change in the mass of the adsorbent was detected. The dried aluminum-based MOF composite adsorbent sample was taken for a compressive performance test. The adsorbent sample to be tested was placed on the lower pressure plate of the compression machine, the machine was started, the upper pressure plate moved downward, pressure was applied to the adsorbent sample, and the pressure resistance value of the material was recorded. For the test results, please refer to Table 1. Weigh 10g of the adsorbent molded particles and spread them evenly on a flat dish, and measure them in a constant temperature and humidity chamber. The temperature of the constant temperature and humidity chamber was set to 30°C, the humidity was set to 30%RH, and the adsorption performance of the adsorbent was tested at a wind speed of 2m / s. For the test results, please refer to Table 1.

[0074]

[0075] Table 1

[0076] In summary, the aluminum-based MOF composite adsorbent prepared by the present invention has strong compressive resistance, and its mechanical properties and stability are significantly improved. Although its water adsorption performance is not as good as that of Al-MOF, the decline is not large, and it still has strong water absorption performance. It can be used in water adsorption materials, especially in adsorption-type air water extraction materials.

[0077] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A method for preparing an aluminum-based MOF composite adsorbent, characterized in that: The following steps are involved: Weigh lithium chloride, add it into deionized water, stir and dissolve it to obtain a lithium chloride solution, weigh Al-MOF, add it into the lithium chloride solution, disperse it by ultrasonic wave, stir, filter it, and dry it at 80-120° C. to obtain an aluminum-based MOF adsorbent; Sodium alginate and carrageenan were weighed separately, added into deionized water at 75-85°C, stirred and dispersed evenly, and cooled to room temperature to obtain a double network hydrogel; The double network hydrogel is added to the aluminum-based MOF adsorbent and mixed evenly, and the adsorbent particles are formed into adsorbent particles through a pelletizing device. The adsorbent particles are dried at a temperature of 80 to 120° C. to obtain an aluminum-based MOF composite adsorbent.

2. The method for preparing an aluminum-based MOF composite adsorbent according to claim 1, characterized in that: The mass ratio of the Al-MOF to lithium chloride is 1:(1.5-2.5), and the concentration of the lithium chloride solution is 30-45 wt%.

3. The method for preparing an aluminum-based MOF composite adsorbent according to claim 1, characterized in that: The preparation method of the Al-MOF is as follows: Add fumaric acid and aminosuccinic acid into deionized water, add sodium hydroxide, and stir to dissolve at a temperature of 30 to 80° C. to obtain a ligand solution; Add aluminum chloride hydrate into deionized water, stir and dissolve at room temperature to obtain a metal salt solution; The metal salt solution is added to the ligand solution, stirred at a temperature of 30 to 80° C. for 2 to 5 hours, the obtained solid product is washed with deionized water for 2 to 3 times, and dried at a temperature of 80 to 120° C. to obtain Al-MOF.

4. The method for preparing an aluminum-based MOF composite adsorbent according to claim 3, characterized in that: The molar ratio of fumaric acid to aminosuccinic acid is (4-5.5):

1.

5. The method for preparing an aluminum-based MOF composite adsorbent according to claim 4, characterized in that: The molar ratio of the sodium hydroxide to the total ligand is (0.5-1.5):1, and the molar amount of the total ligand is the sum of the molar amounts of fumaric acid and aminosuccinic acid.

6. The method for preparing an aluminum-based MOF composite adsorbent according to claim 5, characterized in that: The molar ratio of the aluminum chloride hexahydrate to the total ligand is 1:(3-5).

7. The method for preparing an aluminum-based MOF composite adsorbent according to claim 1, characterized in that: The molar ratio of sodium alginate to carrageenan is (0.5-2):

1.

8. The method for preparing an aluminum-based MOF composite adsorbent according to claim 7, characterized in that: The mass percentage of Al-MOF in the aluminum-based MOF composite adsorbent is 4% to 10%.

9. An aluminum-based MOF composite adsorbent, characterized in that: The aluminum-based MOF composite adsorbent is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the aluminum-based MOF composite adsorbent according to claim 9 in water adsorption materials.

Citation Information

Cited By

  • Hygroscopic hydrogel as well as preparation method and application thereof

    CN120718301A

  • Microporous aluminum-based MOF (Metal Organic Framework) material and application of adsorbent prepared from microporous aluminum-based MOF material in SO2 adsorption and removal

    CN121108512A

  • Wide-humidity-range moisture absorption aluminum-based MOF material and preparation method thereof

    CN121314551A